Chalenges in Thermal Design of Industrial Single-Phase Power Inverter - Ninković, Predrag S (Proceedings, Electrical engineering institute "Nikola Tesla", 2016)
This paper presents the influence of thermal aspects in design process of an industrial single-phase inverter, choice of its topology and components. Stringent design inputs like very high overload level, demand for natural cooling and very wide input voltage range have made conventional circuit topology inapproprate therefore asking for alternative solution. Different power losses calculations in semiconductors are performed and compared, outlining the guidelines how to choose the final topology. Some recommendations in power magnetic components design are given. Based on the final project, a 20kVA single-phase inverter for thermal power plant supervisory and control system is designed and commissioned.